Downward Workplace Mobbing: A Sign of the Times? - Vandekerckhove, Wim (Journal of business ethics, 2003)
This paper offers a speculative elaboration on downward workplace mobbing – the intentional and repeated inflictions of physical or psychological harm by superiors on subordinates within an organization. The authors cite research showing that workplace mobbing is not a marginal fact in today's organizations and that downward workplace mobbing is the most prevalent form. The authors also show that causes of and facilitating circumstances for downward workplace mobbing, mentioned by previous research, match current organizational shifts taking place within a context of globalisation. This paper argues that it is not the organizational shifts themselves which are to "blame", but an inadequate transformation of leadership and power in reaction to those shifts. Using Foucault's power-knowledge-rules of right triad, the authors offer an explanation for downward workplace mobbing beyond the organizational changes themselves. More precisely, as the organizational changes can be characterized by a new power/knowledge bond calling forth new rules of right, downward workplace mobbing could be seen as manifestations of power outside of the delineations drawn by these new rules of right. In other words, downward workplace mobbing is pathology of current organizational shifts, resulting from not acting out the full ethical potential of the discourse of excellence, adventure, creativity and responsibility, which characterizes these shifts.